ANALISIS DAMPAK PEMEKARAN DAERAH TERHADAP PERTUMBUHAN SEKTOR PEREKONOMIAN DI KABUPATEN PONTIANAK - B01108008, Hendri (Jurnal Pembangunan dan Pemerataan, 2013)
This descriptive study has three main objectives, the first objective is to identify and analyze the growth sectors of the economy in Pontianak regency before and after the expansion area, the second objective to identify and analyze the District's economic growth compared with the growth Pontianak West Kalimantan Province before and after expansion area, while the third goal to identify and analyze the competitiveness of the economic sectors in Pontianak regency before and after regional expansion. Period before the expansion area is calculated starting in 2004 until in 2007, while after the split area is calculated from the year 2008 until the year 2011. These results indicate that the growth of economic sectors Pontianak regency after splitting a smaller area than before the expansion area, Pontianak regency economic growth after the split area is also well below the economic growth of the West Kalimantan province, while the competitiveness of economic sectors Pontianak regency decreased after the introduction of regional expansion. Best sector Pontianak regency after the expansion area is mining and quarrying sector as it has the highest growth rate and competitiveness both in the province of West Kalimantan.